The Library as a Social Institution for Organizing Science and Society Interaction (Based on the Materials of Historical Science) - E. A. Pleshkevich (Библиосфера, 2025)
Basing on the materials of historical science, the analysis of the organization of library interaction between science and society is given. It is noted, that the effectiveness of the development of historical self-awareness and worldview is due not only to the state of historical science, but also the organization of interaction between science and society, especially the interpretation of key events in the history of our country, which are the subject of disputes leading to discord in modern Russian society. Using the example of the new chronology, the negative impact of pseudoscientific historical research on the historical worldview and attitude to history in Russian society is shown. The author assumes that the reasons for this is in the 1990s–2010s, when the state has “withdrawn” itself from the sphere of political and natural science education. As a result, the state-oriented educational model of librarianship has been replaced by a personality-oriented model focused on the absolutisation of information and leisure demand and making librarians free from the responsibility for the consequences of using information or a document obtained in the library. Domestic librarianship has gradually transformed from the sphere of education into the sphere of services. That has resulted in the fact – the Russian state has lost one of the effective institutions for promoting scientific and other policies, and the society has become unable to effectively resist the influence of pseudoscientific concepts, implemented in life thanks to marketing technologies. The author assumes that the adoption of the foundations of the state policy of the Russian Federation in the field of historical education adopted in 2024 creates conditions for correcting library construction towards the interests of not only the individual, but also the state and society. It is proposed to take the state-oriented educational model of librarianship, created in the USSR, as the basis. It should be complemented by the harmonization of the interests of the individual, society and the state. The author reveals the following point of view: the involvement of libraries in the implementation of the state policy of historical education should include purposeful acquisition of library collections with recommended scientific and popular scientific literature on history; information and bibliographic provision of historical education, activation of library services and, first of all, reading. The content of this policy is suggested to facilitate the transition to an educational model of librarianship at a qualitatively new updated level.